Speech Systemicity of Scientific Texts: Conceptual Development (On Centenary of M. N. Kozhina's Birth) - M. P. Kotyurova; E. A. Bazhenova (Научный диалог)
This article is dedicated to one of the most significant concepts in functional stylistics — speech systemicity. Introduced into scholarly discourse by M. N. Kozhina, this concept elucidates the linguistic specificity of functional styles. The objective of the article is to examine the scientific text as a speech system that is determined by the epistemic situation. It is asserted that the epistemic situation represents a unity of ontological, methodological, and axiological components of scientific knowledge. The binary properties of the speech system within scientific texts are described: integrity vs. fragmentation, stability vs. instability, and dynamism vs. statism. It is reported that integrity is conditioned by the author's intent and the terminological system of the text; stability arises from the conceptual concretization of the terminological system; and dynamism reflects the author's movement from ignorance to knowledge. Drawing on a synergistic approach, it is posited that the speech systemicity of a text manifests not only in orderliness but also in chaos and asystematicity. The asystematic properties of scientific texts are evident in their elasticity, illusoriness, openness, and emergent content. It is emphasized that the property of speech systemicity fits into various paradigms of linguistic analysis while maintaining coherence and allowing for interpretative variability. The conclusion highlights the considerable explanatory potential of the concept under discussion and its high productivity for functional stylistics and speech studies.